"The Secret Lives of Dennis Phombeah: Decolonization, the Cold War, and African Political Intelligence, 1953–1974". Issue 1 (2nd January 2021) - Brennan, James R.
Abstract: Processes of decolonization in the context of the Cold War provided enormous opportunities for nationalist figures to parlay insider nationalist knowledge into significant metropolitan influence. This article offers an 'agent-focused' rather than 'agency-focused' approach to the study of Cold War intelligence competition in Africa's decolonization through a study of the career of Dennis Phombeah, a Nyasalander by birth and Tanganyikan nationalist figure who came to work for multiple foreign intelligence agencies. While itself a single case study, this article suggest that multiple intelligence agencies placed a high premium on acquiring a basic understanding of the internal politics of newly-independent African countries, which were otherwise rendered deliberately opaque by the states themselves as a common sovereignty-preserving device. Using intelligence records from Britain, Czechoslovakia and Portugal, a picture emerges of cross-rival institutional dependency on informants from the peripheries who were empowered by their years at metropolitan centers, offering a challenging perspective to institutional-focused studies of Cold War intelligence.